2007
DOI: 10.1253/circj.71.766
|View full text |Cite
|
Sign up to set email alerts
|

Fever Associated With Acute Aortic Dissection

Abstract: cute aortic dissection presents with various symptoms; that is, pain, nausea, vomiting, hematemesis, cold sweat, syncope, cerebrovascular accident, ischemic peripheral neuropathy, hypertension, congestive heart failure, shock, cardiac arrest, and sudden death. In addition, fever is often associated with acute aortic dissection and in rare cases is persistent so that it becomes difficult to determine whether or not it is associated with acute aortic dissection. A number of such cases have been reported, 1-4 as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 17 publications
(17 reference statements)
0
24
0
Order By: Relevance
“…Therefore, these 2 biomarkers may be useful in more practical applications. In addition, there have been 4 previous reports that address elevated FDP values in patients with aortic dissection (14)(15)(16)(17), but none of these reports compared the FDP values at the time of patient admission between patients with AAD and control subjects to reveal the usefulness of FDP in diagnosing patients with AAD. Therefore, to the best of our knowledge, this is the first report that has demonstrated sensitivity and negative predictive values of FDP in the initial assessment of AAD, suggesting that the measurement of FDP may be an alternative tool for the measurement of D-dimer levels.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these 2 biomarkers may be useful in more practical applications. In addition, there have been 4 previous reports that address elevated FDP values in patients with aortic dissection (14)(15)(16)(17), but none of these reports compared the FDP values at the time of patient admission between patients with AAD and control subjects to reveal the usefulness of FDP in diagnosing patients with AAD. Therefore, to the best of our knowledge, this is the first report that has demonstrated sensitivity and negative predictive values of FDP in the initial assessment of AAD, suggesting that the measurement of FDP may be an alternative tool for the measurement of D-dimer levels.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8] Of interest, while febrile reaction at presentation of acute aortic dissection is a well-known feature of the disease, chronic aortic dissection in which fever or other symptoms of systemic illness dominate the clinical picture for weeks is distinctly rare, with diagnosis usually made by imaging modalities incidentally in the course of basic investigation. 9,10 The presence of small left sided pleural effusion has been mentioned as a clue for the right diagnosis in this setting. 11,12 The pathogenetic mechanisms of the prolonged systemic response in the course of chronic aortic dissection have not been elucidated yet.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that 85.9% patients with acute aortic dissection had fever after stent, in whom about one-fourth of the patients already had fever the day before stent, which suggested that stent-graft could increase the possibility of fever. The fever associated with aortic dissection involves an inflammatory reaction, which is caused by thrombi, destroyed tissue, and cytokines (7). False lumen thrombosis is the main pathophysiological feature after stent-graft in acute aorta dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Only two papers have been published concerning the characteristics of fever associated with acute aortic dissection (7,8). However, the beginning time and duration of fever after percutaneous endovascular stent-graft in patients with aortic dissection is not well known.…”
Section: Introductionmentioning
confidence: 99%